THE BAD EFFECTS OF FAKE NEWS IN TEACHING: UNDERMINING EDUACATION AND CRITICAL THINKING - Ergashov , Khurmatillo Solijon ugli; Eshchonov , Sanjar Erkinbayevich (Innovative Development in Educational Activities, 2023)
In the digital age, information spreads faster and wider than ever before. While this connectivity has its benefits, it has also given rise to a concerning phenomenon: the proliferation of fake news. Fake news refers to deliberately fabricated or misleading information presented as factual news. This distortion of truth has infiltrated various aspects of society, including education, where its impact can be particularly damaging. The dissemination of fake news in teaching has severe consequences, undermining the educational process and impeding the development of critical thinking skills among students. In this article, we explore some of the detrimental effects of fake news in the realm of education.